2011
DOI: 10.1017/s0033291711002637
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbid anxiety disorders in bipolar disorder and major depression: familial aggregation and clinical characteristics of co-morbid panic disorder, social phobia, specific phobia and obsessive-compulsive disorder

Abstract: Background Co-morbidity of mood and anxiety disorders is common and often associated with greater illness severity. This study investigates clinical correlates and familiality of four anxiety disorders in a large sample of bipolar disorder (BP) and major depressive disorder (MDD) pedigrees. Method The sample comprised 566 BP families with 1416 affected subjects and 675 MDD families with 1726 affected subjects. Clinical characteristics and familiality of panic disorder, social phobia, specific phobia and obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 53 publications
7
64
0
5
Order By: Relevance
“…In the ECA database, OCD-BD patients had statistically significant higher lifetime rates of 'thoughts of suicide', 'suicide attempts', 'thoughts of death', and 'wanting to die' vs. non-OCD-BD patients (3). These features were confirmed in most recent studies both in OCD-BD patients (31,37,39,75) and in BD-OC syndrome patients (16). OCD also was associated with a 2.4-fold increase in the odds of suicidal ideation among BD adolescents as compared to noncomorbid adolescents (45).…”
Section: Included Studiessupporting
confidence: 80%
See 2 more Smart Citations
“…In the ECA database, OCD-BD patients had statistically significant higher lifetime rates of 'thoughts of suicide', 'suicide attempts', 'thoughts of death', and 'wanting to die' vs. non-OCD-BD patients (3). These features were confirmed in most recent studies both in OCD-BD patients (31,37,39,75) and in BD-OC syndrome patients (16). OCD also was associated with a 2.4-fold increase in the odds of suicidal ideation among BD adolescents as compared to noncomorbid adolescents (45).…”
Section: Included Studiessupporting
confidence: 80%
“…In other studies, most BD-OCD subjects either had OCD confined exclusively to depressive episodes or reported worsening of OCD during depression (64); one report showed that in 44% of BD-OCD patients, BD and OCD cycled together (29). When assessed, the total number of depressive episodes was higher in patients with OCD-BD comorbidity than in BD alone (74,75).…”
Section: Included Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…It is noteworthy that the FST is a test that is used widely because of its predictive validity, as it is sensitive to all classes of antidepressant drugs (Borsini & Meli, 1988;Deussing, 2006;Lucki, 1997). In addition, as anxiety is present in the majority of patients with depressive disorder (Fava et al, 2000;Goes et al, 2012), it is well known that antidepressant drugs can also ameliorate anxiety-like depression symptoms. Thus, we also explored anxiolytic-like effects using the EPM as a primary screening test, as well as depressive animal models.…”
Section: Discussionmentioning
confidence: 99%
“…When diagnosed comorbidly with BD, OCD has been associated with an earlier onset of BD, a higher number of previous mood episodes, rapid cycling, seasonality, substance misuse, and lower overall functioning 732, 737, 738, 739, 740, 741, 742. Jeon et al recently conducted a comprehensive review of patients diagnosed with BD and comorbid OCD and found twice the rate of pharmacological switch to mania or hypomania, but suggested this could be due to the more frequent use of antidepressants in that population 732.…”
Section: Specific Populationsmentioning
confidence: 99%